2022
DOI: 10.1155/2022/4512503
|View full text |Cite
|
Sign up to set email alerts
|

PTEN: An Emerging Potential Target for Therapeutic Intervention in Respiratory Diseases

Abstract: Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a potent tumor suppressor that regulates several key cellular processes, including proliferation, survival, genomic integrity, migration, and invasion, via PI3K-dependent and independent mechanisms. A subtle decrease in PTEN levels or catalytic activity is implicated not only in cancer but also in a wide spectrum of other diseases, including various respiratory diseases. A systemic overview of the advances in the molecular and cellular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 152 publications
1
7
0
Order By: Relevance
“…PTEN known for its antagonistic role against the PI3K/Akt pathway, has garnered interest for its functions in maintaining genomic stability, regulating cell survival, proliferation, and metabolism in various conditions including tumors, asthma, idiopathic pulmonary fibrosis, and arthritis. [26][27][28] Earlier investigations have indicated a marked decrease in PTEN concentrations within the peripheral lung tissues of individuals diagnosed with COPD. Importantly, this decrease in PTEN was found to have a direct positive correlation with the intensity of airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN known for its antagonistic role against the PI3K/Akt pathway, has garnered interest for its functions in maintaining genomic stability, regulating cell survival, proliferation, and metabolism in various conditions including tumors, asthma, idiopathic pulmonary fibrosis, and arthritis. [26][27][28] Earlier investigations have indicated a marked decrease in PTEN concentrations within the peripheral lung tissues of individuals diagnosed with COPD. Importantly, this decrease in PTEN was found to have a direct positive correlation with the intensity of airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR‐494‐3p can be activated by oxidative stress in COPD cell model and its knockdown rescues cell senescence and inflammation. 17 Furthermore, PTEN is a well‐established target for therapeutic intervention of COPD, 19 and previous studies mainly discussed the interplay of PTEN with mitochondrial dysfunction, mitophagy, and senescence in COPD. 40 , 41 Less is known about its role in the inflammation state.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphatase and tensin homolog (PTEN) is a genetic regulator of various metabolic changes, including glycolysis, lipid metabolism, and mitochondrial metabolism 18 . PTEN also emerges as a potential target for various chronic lung diseases, including COPD, asthma, pulmonary hypertension, and acute lung injury, and regulates physiological activities ranging from inflammation responses, apoptosis to proliferation 19 . Additionally, the binding of miR‐494‐3p to PTEN 3′UTR sequence was predicted and verified by databases and the dual‐luciferase assay, suggesting miR‐494‐3p‐mediated negative regulation of PTEN in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The authors further confirmed these results in a mouse model, which demonstrated gastric tumor growth upon exosomes expressing lncRNA CRNDE [ 42 ]. The described mechanism is enthralling because it not only reveals how cells of the tumor microenvironment modulate cisplatin resistance but also demonstrates faultlessly how exosomes via lncRNA CRNDE suppress PTEN expression, known as a tumor suppressor [ 76 , 77 , 78 , 79 ].…”
Section: Exosomes As Chemoresistance Mediatorsmentioning
confidence: 99%